Does childhood family structure help create stratification in adult education and labor market attainment?: An argument for the selectivity perspective. Issue 1 (January 2017) - Dufur, Mikaela J.; Alexander, Alyssa J.
Abstract: Stratification in opportunities for and attainment of educational credentials, stable and well‐paying jobs, wealth, and socioeconomic status causes problems for both individuals and the societies they live in. It is unclear, however, the extent to which important childhood experiences, such as family structure and transitions, shapes opportunity paths and eventual attainment later in adulthood. The intergenerational transmission literature suggests little if any role of family structure in later attainment, while family scholars and demographers find more compelling evidence that childhood family structures and transitions are influential in adulthood. We argue that both perspectives may be identifying selectivity processes that help explain potential links between families of origin and differences in opportunities to attain education, careers, and status. We then provide suggestions for future work in each of these scholarly traditions to help untangle both the degree to which family structure does or does not affect adult attainment and whether selectivity is the key explanation for any such relationships.